Anemia Prevalence after Iron Supplementation among Pregnant Women in Midwifes Practice of Primary Health Care Facilities in Eastern Indonesia - Merry M. V. Seu; Johanes C. Mose; Ramdan Panigoro; Edhyana Sahiratmadja (Anemia)
Background. Iron deficiency anemia (IDA) in pregnant women is common, and iron supplementation is given during pregnancy to reduce birth complication. This study aimed to explore the prevalence of anemia and type of anemia after iron supplementation among pregnant women in the eastern part of Indonesia. Methods. A cross-sectional study design was conducted between January and March 2019 in three Primary Health Care (PHC) facilities at Kupang, West Timor. After consent, pregnant women who had taken their iron supplementation for at least 3 months were asked for iron pills intake by using a self-designed questionnaire and by counting the pills leftover. Complete blood count examination was performed, and the type of anemia was assessed using Shine and Lal index (SLI; MCV ∗ MCV ∗ MCH/100) to determine whether anemia was due to iron deficiency or β-thalassemia trait (β-TT). In a subset of iron tablets distributed in the PHCs, Fe-concentration was measured. Results. Of 102 pregnant women included, only 25.5% had taken the pills with a pill count of >80%. Interestingly, Fe-concentration in the pills from three different PHC facilities varied between 75% and 100%. After iron supplementation, however, anemia was detected in 34.3%, and based on SLI, 14.7% was suspected because of iron deficiency and 19.6% was suspective of β-TT. Of note, nonanemic pregnant women (17.6%) had also low SLI, suggesting β-TT or other hemoglobinopathies. Conclusion. Assessment of Shine and Lal index as the first step to screen the type of anemia in pregnant women from a limited area is of potential value, especially because Indonesia is located in the thalassemia belt area. An integrative approach and counseling among pregnant women with β-TT and their partners will increase thalassemia awareness and optimal birth management.